Crack healing induced electrical and mechanical properties recovery in a Ti2SnC ceramic. Issue 1 (January 2016) - Li, Shibo; Bei, Guoping; Chen, Xiaodong; Zhang, Linquan; Zhou, Yang; Mačković, Mirza; Spiecker, Erdmann; Greil, Peter
Abstract Ceramics are able to heal cracks and flaws by triggering local sintering (internal cracks) or oxidation reaction (surface cracks) which may induce the recovery of mechanical strength. Crack healing in ceramics, however, is limited to micro-sized cracks and requires elevated temperatures (above 1000 °C) and long time periods even up to 100 h. In this work we report on accelerated crack healing of a Ti2SnC ceramic which is capable to repair thermal shock induced cracks at a relatively low temperature of 800 °C within only 1 h. After healing treatment both the low flexural strength and electrical conductivity measured on the damaged material after quenching were almost fully recovered. Furthermore, Ti2SnC exhibits repeatable healing capability which offers a high potential for developing durable ceramics with prolonged lifetime under harsh thermal conditions.